How Much Quantum Confusion Does it Take to Catch an Eavesdropper. - Oswald, Boaz; Van Huele, Jean Francois (Journal of the Utah Academy of Sciences, Arts & Letters, 2025)
Quantum cryptography uses the inherent quantum uncertainty in polarization of photons and the inability to copy quantum states to catch an eavesdropper in communication channels carried by light. If a polarization is detected in a frame rotated from the frame it was sent in, it gives probabilistic results. In the original version of the well-known BB84 cryptography protocol, sender and receiver agree on two fixed bases, rotated by 45 degrees, to send and receive the photons. The ambiguity in bases forces an eavesdropper to intercept and forward possibly wrong polarizations, thereby revealing their presence. We explore the effect of increasing the number of bases and attempt to maximize the probability of detecting the eavesdropper. We show that, maybe surprisingly, this probability does not depend on the number of bases.